TINDAK TUTUR ILOKUSI DOSEN DENGAN MAHASISWA DALAM PROSES PEMBELAJARAN MATA KULIAH BAHASA INDONESIA KELAS BK 1A TAHUN AJARAN 2019/2020 - M. Iqbal Tawakkal (An-Nas, 2022)
“This study examines the illocutionary acts of lecturers and students in the Indonesian language learning process for class BK 1 A. This study aims to (1) describe the illocutionary acts of lecturers and students in the process of learning Indonesian language BK 1 A, and (2) the purpose of the illocutionary acts of lecturers and students in Indonesian language learning class BK 1 A. This type of research is descriptive qualitative. The research technique used in this study is a competent listening and recording technique. The data collection technique was used by researchers to obtain comprehensive data regarding the types of illocutionary speech acts during the learning process. The data analysis technique in this study uses an interactive model analysis consisting of four paths, namely, data collection, data reduction, data presentation, and conclusion drawing/verification. The results of this study found 78 data on illocutionary speech acts according to Austin, which consist of 6 vermiculite speech acts, 68 exclusive speech acts, and 4 commissive speech acts. The speech acts found have different purposes and factors in speaking according to the situation and context. Every communication will be successful if the speaker understands the speaker's intent.”